Cost optimization of multiunit construction projects using linear programming and metaheuristic-based simulated annealing algorithm - Podolski, Michał; Sroka, Bartłomiej (Journal of Civil Engineering and Management, 2019)
The article presents the cost optimization model for multiunit construction projects. Multiunit projects constitute a special case of repetitive projects. They consist in the realization of many different, when it comes to size, types of residential, commercial, industrial buildings or engineering structures. Due to the specific character of construction works, actual schedules of such projects should not only take into account real costs of construction, but also be subject to specific restrictions, e.g. deadlines for the completion of units imposed by the investor. To solve the NP-hard problem of choosing the order of units’ construction there was metaheuristic algorithm of simulated annealing used. The objective function in the presented optimization model was the total value of the project cost determined on the basis of the mathematical programming model, taking into account direct and indirect costs, costs of missing deadlines and costs of work group discontinuities. In the article, an experimental analysis of the proposed method of solving the optimization task was carried out in a model that showed high efficiency in obtaining suboptimal solutions. In addition, the operation of the proposed model has been presented on a calculation example. The results obtained in it are fully satisfying.